CO39 | Artificial intelligence in hemophilia management: challenging the need for experts (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: Hemophilia is a rare genetic disorder characterized by deficiencies in Factor VIII or Factor IX, which can lead to spontaneous and prolonged bleeding episodes, as well as bleeding caused by minor trauma. This occurs most frequently in patients with severe hemophilia who have not initiated early prophylactic treatment or who do not receive prompt administration of clotting factor concentrates in response to bleeding events. Traditionally, specialized hematologists and dedicated Hemophilia Treatment Centers have been essential for accurate diagnosis and effective management of the disease. However, the recent advancement of artificial intelligence (AI) in healthcare has raised important questions regarding its potential to replace specialist physicians in disease management. This study aimed to evaluate the diagnostic and therapeutic accuracy of five AI models (ChatGPT (OpenAI), Gemini (Google), Copilot (Microsoft), DeepSeek AI and Perplexity AI) in responding to fundamental knowledge-based questionnaires on hemophilia and complex clinical scenarios.